Substrate based zooperiphyton communities and some physicocehmical features of Dhanmondi lake, Dhaka, Bangladesh - Hosain, Md Eilious; Kabir, AKM Nazrul; Naser, M Niamul (Bangladesh Journal of Zoology, 2015)
This study deals with the zooperiphyton communities of Dhanmondi lake, Dhaka, Bangladesh using bamboo, mehegoni and rain tree sticks as substrates along with some physicochemical features of the lake water. It was revealed that zooperiphyton communities constitute protozoa, rotifera, copepoda, cladocera, ostracoda, conchostraca, insect larvae, oligochaeta, nematoda and mollusca. Rotifera (41%), protozoa (31%) and ostracoda (14%) were the dominant groups of zooperiphyton. Among protozoans, Epistylis sp. (52%) and Arcella sp. (20%); among rotifera, Rotaria neptunia (32.88%), Anuraeopsis fissa (17%) and Brachionus angularis (12%); among copepoda, naupleus (52%) and Cyclops sp. (32%); among cladoceran, Chydorus sp. (28%); among ostracods, Cypris sp. (100%); among molluscs, Bellamya sp. (75%) and Brotia sp. (22%) were found to be the most dominant species. The average number of zooperiphyton was 43023.55 ± 5891.34 individual m-2 recorded from all substrates. During the study period, the physicochemical features of water of Dhanmondi lake were found to be suitable for aquatic biota. It can help in enhancing the productivity as well as sustain the aesthetic value of the lake. Bangladesh J. Zool. 41(1): 61-71, 2013